Hybrid DCT/Pixel Domain Architecture for Heterogeneous Video Transcoding - Shanableh, Tamer (2003)
In this paper the pixel domain heterogeneous video transcoder proposed by the authors is implemented in the DCT domain. Consequently, the motion compensation and its inverse and the image down-sampling functions of the pixel domain transcoder are implemented in the frequency domain whilst eliminating the DCT and IDCT pairs. Moreover the paper proposes two transcoding architectures. In one, the transcoder is simplified by implementing both its MC-loops in the DCT domain. While in the other, image decimation is realised through a modified inverse transformation of the top-left 4x4 coefficients. The input and output domains of the mentioned decimator render the decoder’s and the encoder’s MC-loops to be in the DCT domain and the pixel-domain respectively. This results in a unique hybrid DCT, pixel domain transcoding architecture. Various methods for accelerating the process of the DCT domain motion compensation are reviewed and classified into lossless and lossy methods. It is shown that both picture quality and performance are enhanced by utilising shared information with successive motion compensated macroblocks. The superiority of the hybrid architecture is then assessed in terms of preserving image quality, feasible functionality and tolerance to lossy acceleration of the DCT domain MC.